IMPLEMENTASI PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK-EMKM) PADA UKM DAVIN DECOR SURAKARTA - Judianto, Rochmad; Ismunawan, Ismunawan; Rahman, Arief Nugroho (JAB (Jurnal Akuntansi & Bisnis), 2018)
Financial Accounting Standards - Micro, Small and Medium Enterprises (SAK EMKM) are expected to be a solution to the problems that often hit Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The problem faced by MSMEs is the unavailability of structured and systematic records in good financial statements according to the EMKM standard. MSMEs should be able to make and publish financial reports that can be accounted for and understood by internal and external parties. The EMKM SAK which came into effect as of January 1, 2018 should have been known or implemented by MSMEs. The purpose of this study is to find out the preparation of Davin Decor & Interior SME financial reports based on SAK EMKM and to find out the obstacles faced by Davin Decor & Interior SMEs in implementing the SAK EMKM. The technique used to collect data through interviews and observations made at the business location of Davin Decor & Interior. The data analysis technique uses descriptive analysis techniques. The results of the study reveal that financial reporting on SMEs is still very simple, not in accordance with the SAK EMKM. This happens because of the lack of support from the company owner, educational background, and also due to the lack of maximum role of the government and institutions in charge of SMEs in the dissemination and training of MSME business actors.Keywords: EMKM financial accounting standards, MSMEs, MSME Financial Reports, SAK-EMKM Financial Reports